Forward-secure ciphertext-policy attribute-based encryption scheme - EIJiang-hong W; IUWen-fen L; UXue-xian H (Tongxin xuebao)
To mitigate the damage of key exposure in the context of ciphertext-policy attribute-based encryption (CP-ABE). The syntax and security model of forward-secure CP-ABE was presented. Then, a concreted forward-secure CP-ABE scheme was constructed. Under the l-BDHE assumption, the proposed scheme was proved secure in the stan-dard model. Furthermore, the performance of the proposed scheme was discussed in terms of security and efficiency. The results demonstrate that the proposed scheme strengthens the security of CP-ABE, without getting overmuch cost of computation and storage, and thus is more feasible for practical applications.